2021
DOI: 10.3390/vaccines9080832
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Attitudes towards the COVID-19 Vaccine and the Willingness to Get Vaccinated among Adults in Poland: Analysis of Serial, Cross-Sectional, Representative Surveys, January–April 2021

Abstract: In December 2020, the first coronavirus disease 2019 (COVID-19) vaccine was authorized in the European Union. This study aimed to assess the changes in attitudes towards the COVID-19 vaccine and the willingness to get vaccinated among adults in Poland between January and April 2021. Secondary data analysis was carried out using data obtained from nationally representative cross-sectional surveys (four consecutive waves: January 2021, n = 1150; February 2021, n = 1179; March 2021, n = 1154; April 2021, n = 1131… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…The existing body of research on vaccine hesitancy has shown in Poland a high and relatively stable level of scepticism that even preceded the actual vaccine rollouts [1,28,48,51]. The models implied the existence of even more long-term factors-demographic variables from 2011 or voting patterns from 2015 still had high predictive value in 2021, suggesting underlying patterns unrelated to any recent public opinion swings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing body of research on vaccine hesitancy has shown in Poland a high and relatively stable level of scepticism that even preceded the actual vaccine rollouts [1,28,48,51]. The models implied the existence of even more long-term factors-demographic variables from 2011 or voting patterns from 2015 still had high predictive value in 2021, suggesting underlying patterns unrelated to any recent public opinion swings.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them were carried out at a time when a vaccine was a distant solution, and others during the vaccination campaigns in individual countries. They were conducted in Poland [1,2], the United States [3][4][5][6][7], Ireland and the United Kingdom [8,9], Australia [10], Canada [11], France [12], Italy [13][14][15], Portugal [16], Finland [17], Greece [18], China [19,20] and Japan [21]. As a result of multicentre cooperation, surveys in seven European countries [22], seven European countries and the United States [23], three Asian and five African countries [24], 23 Arab countries and territories [25] and 19 countries with a high COVID-19 burden [26] have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…In November 2020, only 20% of Poles declared a willingness to vaccinate, and this figure increased to 55% in mid-February 2021 [42,43]. However, during the first four months of 2021, approximately 30% declared a lack of willingness to receive any COVID-19 vaccine, with the main concern related to the potential side effects [44]. Until the present study was initiated, only 50% of the Polish population was fully vaccinated (and 51% received at least one dose) despite extensive science communication efforts and the worsening pandemic situation in the country, encompassing nearly 1.6 million new cases and 47 thousand deaths between January and September 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention in Poland, apart from the restrictions regulated by law, has also consisted in introducing vaccinations as early as possible. The first vaccination day in this country was 27 December 2020 [18]. By 11 October, 52.61% of Poles were vaccinated, including 51.7% fully vaccinated [19].…”
Section: Discussionmentioning
confidence: 99%
“…We are afraid that vaccination of nearly half of the population will be insufficient and that we will observe an increase in infections, i.e., a "fourth wave". The Polish government is doing a lot to increase the percentage of vaccinated people: it has organized, among others, information campaigns and contests with prizes, has introduced advertisements on TV and other mass media, has launched touring vaccination points and vaccination in pharmacies and shopping malls [18,20].…”
Section: Discussionmentioning
confidence: 99%